Towards Bio-based Flame Retardant Polymers - Sonnier, Rodolphe (Biobased Polymers,, 2018)
Sustainable development has become a great concern in modern society. The authors of this brief describe how one strategy to reach this objective is to replace oil-based materials with bio-based materials. They emphasize the great efforts that have been made to synthesize new bio-based polymers or additives or to replace glass fibers by natural fibers in composites. Flame retardancy is one of the most desired properties for many applications in wires and cables, building, transport, electric and electronic devices. The authors of this fascinating and timely brief summarize this important field in three parts. The flame retardancy of biobased polymers, the flame retardancy of natural fibers composites, and the synthesis and efficiency of biobased flame retardants.